ROLE OF VISUAL LITERACY IN LANGUAGE ACQUISITION - Nematullaeva , Muslimakhon Rakhmatullo kizi (Innovative Development in Educational Activities, 2024)
Visual literacy significantly contributes to language acquisition by enhancing learners’ understanding and retention of linguistic concepts. This article is devoted to highlighting the importance of visual aids in language learning across various educational contexts. Through an extensive literature review, it examines how visual literacy influences language acquisition, elucidating effective strategies for integrating visual elements into language teaching methodologies.